Effects of Nigella sativa oil extract on inflammatory cytokine response and oxidative stress status in patients with rheumatoid arthritis: a randomized, double-blind, placebo-controlled clinical trial - Vahid Hadi; Sorayya Kheirouri; Mohammad Alizadeh; Alireza Khabbazi; Hossein Hosseini (Mashhad University of Medical Sciences, 2016)
Objectives: Nigella sativa is a medicinal plant that has long been used in traditional medicine for treating various conditions. Numerous animal studies provided evidences that the seed may elicit a broad anti-inflammatory/anti-oxidant activity. The aim of the present clinical trial was to evaluate anti-inflammatory and antioxidant properties of Nigella sativa oil in patients with rheumatoid arthritis (RA). Materials and Methods: Forty-two patients with RA were assigned into two groups in this randomized, double blind, placebo-controlled clinical trial. Subjects in intervention group received two capsules, 500 mg each, of Nigella sativa oil, each day for 8 weeks. The other group consumed two capsules as placebo per day for the same period of time. Serum TNF-α, IL-10, and whole blood levels of oxidative stress parameters were measured at baseline and end of the trial. Results: The serum level of IL-10 was increased in the Nigella sativa group (p